1969
DOI: 10.1104/pp.44.5.631
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene-controlled Induction of Phenylalanine Ammonia-lyase in Citrus Fruit Peel

Abstract: Abstract. L-Phenylalanine ammonia-lyase (PAL) activity is low in the external layers (flavedo) of intact mature grapefruit peel. Flavedo discs evince upon incubation increasing PAL activity and ethylene production. Light has no effect in enhancing PAL activity in discs. Exogenous ethylene stimulates PAL activity in the flavedo of intact mature grapefruits (half maximum stimulation at 15 ppm); such activity rapidly decreases when fruit is removed from the ethylene oontaining atmosphere. Carbon dioxide inhibits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
1
2

Year Published

1973
1973
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(37 citation statements)
references
References 21 publications
(28 reference statements)
1
33
1
2
Order By: Relevance
“…They suggested that hydroxylation and methylation of naringenin to form hesperetin occurred after glycosylation as the chalcone isomerase did not isomerize neohesperidin chalcone (25). This is in contrast to other plants where hydroxylations and methylations occur before glycosylation (13,14 (13,14) have been found in Citrus tissues, including phenylalanine ammonia-lyase (23,26,30), cinnamate 4-hydroxylase (15) and chalcone isomerase (23,28). The chalcone isomerase from Citrus peels catalyzed the reversible conversion of chalcones to their isomeric flavanones (28).…”
contrasting
confidence: 40%
“…They suggested that hydroxylation and methylation of naringenin to form hesperetin occurred after glycosylation as the chalcone isomerase did not isomerize neohesperidin chalcone (25). This is in contrast to other plants where hydroxylations and methylations occur before glycosylation (13,14 (13,14) have been found in Citrus tissues, including phenylalanine ammonia-lyase (23,26,30), cinnamate 4-hydroxylase (15) and chalcone isomerase (23,28). The chalcone isomerase from Citrus peels catalyzed the reversible conversion of chalcones to their isomeric flavanones (28).…”
contrasting
confidence: 40%
“…Ehylene induces the appearance of PAL activity in citrus flavedo (15). The wound-ethylene produced from flavedo discs induced strong PAL activity in the disc tissue within 24 hr (0.36 + 0.02 ,umol cinnamic acid/g fresh wt/hr).…”
Section: Resultsmentioning
confidence: 99%
“…Sugars were visualized by spraying with 0.1 M p-anisidine and 0.1 M phthalic acid dissolved in 96% ethanol and heating at 100 C for 10 min (I 1). Phenylalanine ammonia lyase (PAL)3 activity was determined according to Riov et al (15).…”
Section: Methodsmentioning
confidence: 99%
“…3 and 5). If ethylene had a role in conjugation, ethylene evolution should have preceded the rise in NAAsp (12,29). However, in the case of pea roots auxin-induced ethylene evolution and growth inhibition occur simultaneously (12).…”
Section: Discussionmentioning
confidence: 99%